Beginning ASP.NET MVC 4 - Paz, José Rolando Guay (Apress Imprint: Apress, 2013)
By now you'll have heard of ASP.NET MVC. This exciting new approach to developing ASP.NET web applications has taken the development world by storm over the last few years. Now a mature technology suitable for mainstream use, its adoption has exploded in recent times. Until recently, ASP.NET MVC was regarded as an advanced technology only suitable for experienced developers with a strong knowledge of classic ASP.NET and C# coding behind them. This book overturns that prejudice and shows that the beautiful simplicity of ASP.NET MVC is just as suitable for novice developers venturing into real-world application design for the first time. With the aid of a fully worked demo application this book explains and demonstrates for you the three pillars of MVC in action. You'll see howthe Model, View and Controller patterns work together in a compliementary manner to provide MVC's powerful results. There's never been a better time to learn how to use ASP.NETMVC 4. The technology will speed your development times, reduce the verbosity of your code and simplify your application designs all at once. Take the first step towards ASP.NET MVC mastery with Beginning ASP.NET MVC 4.